2006
DOI: 10.1530/rep.1.00808
|View full text |Cite
|
Sign up to set email alerts
|

Expression and adaptive regulation of amino acid transport system A in a placental cell line under amino acid restriction

Abstract: Trans-placental transport of amino acids is vital for the developing fetus. Using the BeWo cell line as a placental model, we investigated the effect of restricting amino acid availability on amino acid transport system type A. BeWo cells were cultured either in amino acid-depleted (without non-essential amino acids) or control media for 1, 3, 5 or 6 h. System A function was analysed using a(methyl-amino)isobutyric acid (MeAIB) transcellular transport studies. Transporter (sodium coupled neutral amino acid tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…SNAT2 has an amino acid response element in its promoter region, possibly explaining these findings (Palii et al, 2004). BeWo protein expression for SNAT2 was unaffected in substrate deprivation experiments but there was increased localisation of this isoform to the plasma membrane (Jones et al, 2006). This suggests a similar mechanism to that present in other cell types is responsible for adaptive regulation of system A in placenta.…”
Section: Regulation Of System a By External Factorsmentioning
confidence: 86%
See 1 more Smart Citation
“…SNAT2 has an amino acid response element in its promoter region, possibly explaining these findings (Palii et al, 2004). BeWo protein expression for SNAT2 was unaffected in substrate deprivation experiments but there was increased localisation of this isoform to the plasma membrane (Jones et al, 2006). This suggests a similar mechanism to that present in other cell types is responsible for adaptive regulation of system A in placenta.…”
Section: Regulation Of System a By External Factorsmentioning
confidence: 86%
“…In various cell types, substrate regulation of system A is associated with specific changes in the expression and localisation of SLC38A2/SNAT2 (Franchi-Gazzola et al, 2001;Hyde et al, 2001;Ling et al, 2001). In studies using BeWo choriocarcinoma cells, MeAIB transport has been shown to increase following substrate deprivation and this was associated with upregulation of SLC38A2 mRNA (Jones et al, 2006;Novak et al, 2006b). SNAT2 has an amino acid response element in its promoter region, possibly explaining these findings (Palii et al, 2004).…”
Section: Regulation Of System a By External Factorsmentioning
confidence: 99%
“…In several cell types, amino acid deprivation results in upregulation of system A amino acid transporter activity (37)(38)(39)(40), including the trophoblast-like human choriocarcinoma cell line BeWo ( 38,40 ). Amino acid deprivation increases SNAT2 expression in BeWo trophoblast-like cells ( 38,40 ).…”
Section: Silencing Tlr4 Prevents Oleic Acid Stimulation Of System a Amentioning
confidence: 99%
“…Amino acid deprivation increases SNAT2 expression in BeWo trophoblast-like cells ( 38,40 ). In cell types other than trophoblast cells, activation of JNK signaling has been implicated as an important component in the adaptive response to amino acid deprivation ( 37,39 ).…”
Section: Silencing Tlr4 Prevents Oleic Acid Stimulation Of System a Amentioning
confidence: 99%
“…System A is subjected to extensive regulation, and, in the placenta, it has been shown to be inhibited by IL-1␤ (64), hypoxia (48), nitric oxide (NO) formation (37), hyperglycemia (21), and growth hormone (20). Insulin (27,36), IGF-I (35), EGF (5), amino acid deprivation (34), cortisol (33), and leptin (27) all stimulate system A transport. The regulation of placental system L and TAUT is less well established.…”
mentioning
confidence: 99%